Interview of Richard G. Dickerson by Brian Shoemaker - Dickerson, Richard G. (Byrd Polar Research Center Archival Program, 2005)
Jack Porter, pp. 7 Eddie Saunders, pp. 7 ________Greenwell, pp. 13 Admiral Reed, pp. 13-14, 19, 22, 26, 31, 55 Cdr. Kelly, pp. 14, 18 Sgt. ______ Crane, pp. 17 Lowell Thomas, pp. 17, 26, 30 __________Imboden, pp. 17 __________Roberts, pp. 29 Eddie Goodale, pp. 29 Admiral Richard E. Byrd, pp. 22 __________Curlander, pp. 31 Max Brewer, pp. 35, 44, 53, 63, 65 John Schindler, pp. 45-47, 53, 64-65 Bob Murphy, pp. 45, 58 Kenny Toovak, pp. 47 “Jackass” Cornet, pp. 48 Warren Denner, pp. 51 Betty Dickerson, pp. 53, 57 Admiral Tyree, pp. 54, 56-57 Bo Buck, pp. 59 (Beau Buck, pp. 73??? Same person???) Ed Donnelly, pp. 64 __________Zimmerman, pp. 65-66 __________Felder, pp. 65-66 Chuck Conroy, pp. 71 The media can be accessed at the links below. Audio Part 1: http://streaming.osu.edu/knowledgebank/byrd/oral_history/Richard_Dickerson_1.mp3 Audio Part 2: http://streaming.osu.edu/knowledgebank/byrd/oral_history/Richard_Dickerson_2.mp3 Cdr. Dickerson joined the Navy in December 1941. He was sent to Corpus Christi for flight school. He was with the anti-sub patrol in the Pacific during World War II. After the Korean War, Dickerson volunteered to fly C-130s in Antarctica. On the flight from Cape Town to McMurdo, Lowell Thomas was a passenger. Cdr. Dickerson lived on the Ross Ice Shelf for three seasons. After 23 years in the Navy, he returned to Alaska. He accepted a position on an ice patrol for two submarines in the Artic Ocean. He also flew supplies to the Artic Research Lab on an ice island. His next job was with Evergreen. Major Topics Dickerson’s career in the Navy Flying C-130s with skis attached Difference between a runway and a ski-way Seasonal activities on the Ross Ice Shelf The use of dogs for transportation Establishment of a runway on ice island T-3 in the Arctic The Artic Research Lab Ice Station II (ARLIS II) AJAX Operation The use of Eskimo labor AIDJEX project Construction of the Alaskan Pipeline Landing at Russian bases in the Antarctic Funded by a grant from the National Science Foundation.